2018
DOI: 10.1016/j.jct.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and thermodynamic properties of the amino- and carboxamido-functionalized C-60-based fullerenes: Towards non-volatile carbon dioxide scavengers

Abstract: 1) PRAMO, Saint Petersburg, Leningrad oblast, Russian Federation.(2) P.E.S., Vasilievsky Island, Saint Petersburg, Leningrad oblast, Russian Federation. Abstract. Development of new greenhouse gas scavengers is actively pursued nowadays.Volatility-caused solvent consumption and significant regeneration costs associated with the aqueous amine solutions motivate search for more technologically and economically advanced solutions. We hereby used hybrid density functional theory to characterize thermodynamics, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…It should be noted that although changes in reaction energies and energy barriers when going from gas-phase to solution obtained with the PCM model are trustworthy, the absolute solvation energies are likely overestimated. 57 The harmonic oscillator model of aromaticity (HOMA) index, 58,59 the multicenter index (MCI), 60 and the normalized version of MCI (I NB ) 61 were used to quantify the aromatic character of the 5-and 6-MRs of C 60 . 62 The HOMA is defined as:…”
Section: Methods (A) Computational Methodologymentioning
confidence: 99%
“…It should be noted that although changes in reaction energies and energy barriers when going from gas-phase to solution obtained with the PCM model are trustworthy, the absolute solvation energies are likely overestimated. 57 The harmonic oscillator model of aromaticity (HOMA) index, 58,59 the multicenter index (MCI), 60 and the normalized version of MCI (I NB ) 61 were used to quantify the aromatic character of the 5-and 6-MRs of C 60 . 62 The HOMA is defined as:…”
Section: Methods (A) Computational Methodologymentioning
confidence: 99%
“…5), we found that it is impossible to explain the effect of the cationic reactant by the hydrophilicity of the respective grafting site following the earlier elaborated methodology. 58,59,78 Compare the electronegativity of nitrogen (3.04) to the electronegativity of sulfur (2.58) to the electronegativity of phosphorus (2.19). 79 A more electropositive cationic center donates a larger fraction of the electron density to the a-carbon atoms.…”
Section: Partial Charge Distributions and Geometriesmentioning
confidence: 99%
“…Regarding the case of helicene, three experiments were carried out involving: (a) the addition of all the torsions involving atoms C (15) , C (20) , C (21) , C (24) , C (25) , and C (26) with the C (9) −C (14) bond acting as pivot; (b) addition of all angles involving atoms C (15) , C (20) , C (21) , C (24) , C (25) , and C (26) , with atom C (9) functioning as apex; and c) addition of the interatomic distances (pseudobonds): 26) , and C (21) •••C (25) . In all cases, the description of the vibrational mode at 48.8 cm −1 remained essentially unchanged.…”
Section: Comparison Between Ped and Vmardmentioning
confidence: 99%
“…Indeed, vibrational spectroscopic techniques, such as Fourier transform infrared (FTIR) and Raman spectroscopy permeate the chemical literature, providing valuable insights for the elucidation of molecular structures, , the organization of molecular clusters, the role on interion interactions in ionic liquids, , as well as insights on the organization of novel nanostructured materials. In latter years, theoretical predictions became essential tools, aiding in the interpretation of IR and Raman spectra . In addition to the aforementioned applications, theoretical predictions are a valuable aid in identifying the product of chemical reactions out of several possible outcomes, and also allow the calculation of the thermodynamic and kinetic parameters of these reactions. …”
Section: Introductionmentioning
confidence: 99%